Diversity and Growth Forms of Tree Ferns in the Permian from the Parnaíba Basin (Central-North Brazil) - Vieira Tavares, Tatiane Marinho; Rohn, Rosemarie [UNESP]; Neregato, Rodrigo; Rößler, Ronny; Noll, Robert; Kurzawe, Francine; Conceição, Domingas Maria da; Cisneros, Juan Carlos; Iannuzzi, Roberto; Silva Belem, Antonio Rhamon da; Coutinho, Barbara Karollyni (Springer Nature, 2024)
In north-central Brazil, the Cisuralian of the Parnaíba Basin bears very beautiful and well-preserved petrified tree fern stems and leaves. Some are found in inland sea/lacustrine deposits of the Pedra de Fogo Formation, but the majority are in fluvial system deposits of the lower Motuca Formation. Sedimentation probably occurred in semi-arid conditions with marked dry and wet seasons. Rare gymnosperms in the eastern region of the basin were preserved in situ, but the fossil record is mainly composed of tree fern stems preserved in a horizontal position, sometimes with basal root mantle and reaching 12 m in length. Plants have been uprooted from a probable riparian vegetation, simply toppled over or were carried away during large floods. Tree ferns are chiefly represented by Marattiales stems, for the most part Tietea singularis, a smaller proportion of Psaronius (P. brasiliensis, P. arrojadoi, and P. sinuosus), some fertile pinnae/pinnules with xeromorphic characters (Buritiranopteris costata) and rachises/petioles (Stipitopteris and another morphotype). There are also fossil-taxa of Filicales (Grammatopteris freitasii, Botryopteris nollii) and an uncertain fossil-taxon (Dernbachia brasiliensis). A priori, all tree ferns were endemic, at least to the Brazilian basins. Tietea singularis and Psaronius arrojadoi were the only identified species that dispersed southward to the Paraná Basin after the Permo-Carboniferous glaciation. The fossil Filicales apparently had a closer phylogenetic relationship to northern taxa than the Marattiales. During the Permian, floristic provincialism must have been truly remarkable despite Pangea’s large continental extension or the limited fossil distribution was an effect of preservation.